Modeling of clear-water contraction scour for an abutment bridge in a compound channel - Ghazvinei, Pezhman Taherei (2014)
Bridge collapse has dramatic consequences in transportation system. Besides losing of life, disruption in service results tremendous effects on the economic growth of the countries. Contraction scour is a common and major cause of bridge failure. Designing the bridge foundation safely needs an accurate estimation of scour depth, underestimation may lead to bridge failure while over estimation will lead to excessive construction cost. Abutment bridges most commonly are used for bridges overcomparatively small channels. Reliability, strength and economy are the main reasons to increase concerning in Abutment Bridges. Commonly, in the compound channels, Abutment Bridgesare protrudedinto the main channel. Consequently, contraction scour expands in the main channel. Prior design approaches treated abutments as being solid structure locating in a floodplain or main channel, individually. The main deficiency of previous studies is that they do not accurately simulated the actual constriction features of Abutment Bridge in a compound channel with a complex geometries. Subsequently, the data and observations lead to unrealistically scour depth estimates. The main objective of the current research is to provide reliable prediction of geometrical characteristics for protruded abutment bridge in the compound channel on contraction scour depth and its’ location. The study required extensive experimentation conducted with laboratory flume, and abutments of realistic design that were subjected to the contraction scour for a range of channel constriction, channel geometries, and embankment protection layers. The experiments on clear-water conditions under steady flow at threshold velocity were conducted at an Abutment Bridge with approach embankment configured in a range of erodiblity conditions: fixed embankment on erodible and then far less-erodible floodplain; riprap, gabion-mattress, and non-erodible embankment on readily erodible floodplain. Flow depth was kept constant for all of the experiments with thecohesionless uniform sediment. A methodology is developed to predict the maximum contraction scour depth and its’location along the compound channel. Outcomes of verifying the method show that proposed method gives reasonable maximum contraction scour depth and location predictions. The results indicate that the contraction degree, abutments’ protrusionfrom floodplain into the main channel, soil, and protection layer properties really affect the final contraction scour depth and its’ location. Results allow promoting the Abutment Bridges’ design and consequently increasing economical and public safety by decreasing the bridges’ construction cost, saving additional maintenance charges, increasing bridges’ stability, and preventing loss of lives.However, application of the currently developed methodology are limited to laboratory conditions. Site verifications are necessary in the future study.